Civil Disobedience and Its Impact on Democratization During Abdullah Badawi`s Era - Zawiyah Mohd Zain; Mohammad Agus Yusoff (Penerbit UKM, 2012)
Upon being elected as Prime Minister in 2003, Abdullah Badawi promised to make changes in the political and administrative aspects. However, four years into his leadership, the promise remained unfulfilled and this led to the dissatisfaction among the people. The purpose of this paper is to analyze the emergence of civil disobedience during Abdullah Badawi’s era and its impact upon the election and democratization process. This article argues that civil disobedience occurred due to four factors, namely unfulfilled promise to reform, economic problem, corruption in government and the government’s failure to handle racial issues. Consequently, the National Front coalition failed to gain the two-thirds majority of seats during the 2008 parliamentary general elections and at the same time lost five states to the opposition. Second, even though the emergence of civil disobedience failed to create a change of government, however, it has been able to give birth to cyber democracy and create awareness among Malaysians to challenge the Abdullah Badawi’s leadership of the government.